The relationship between cell apoptosis dysfunction and FEN1 E160D mutation in lupus nephritis patients - Jing Wang; Ping Cao; Yuan-Yuan Qi; Xue-Ping Chen; Li Ma; Rong-Rong Deng; Li-li Zhang; Yu Zhao (Taylor & Francis Group, 2017)
Objective: This study aims to evaluate the role of FEN1 E160D mutation in lupus nephritis (LN) patients with cell apoptosis dysfunction. Methods: (1) Cell apoptosis was detected from 50 paraffin samples obtained from renal biopsies of patients with Class IV LN by TUNEL method and the relationship of the systemic lupus erythematosus disease activity index 2000 (SLEDAI 2000) and renal tissue cell apoptotic index (AI) was discussed. (2) FEN1 gene 61563142-61563342 containing E160D were analysed by extracting genomic DNA from peripheral blood collected from the above 50 LN patients and 25 patients with nephrectomy caused by renal trauma. The difference between these two groups was statistically significant. Results: Cell apoptosis was detected in all patients with LN, and correlation analysis results revealed a positive relationship between SLEDAI 2000 and AI (r = 0.39, p = .032). The FEN1 gene 61563142-61563342 fragment had site mutations at C/− (+61563189), A/T (+61563198), A/− (+61563204), G/T (+61563303), and T/C (+61563304). However, no statistical significance was found between LN patients detected with cell apoptosis and healthy individuals. Conclusions: This study revealed that cell apoptosis dysfunction plays a key role in the pathogenesis of LN, even though the difference in FEN1 gene 61563142-61563342 between LN patients and healthy individuals was not statistically significant. Larger sample size studies or genome-wide association studies are needed.